Implementation of the Axiological Potential of a Publicistic Text in Teaching the Russian Language: Methodological Tools - Olga N. Levushkina; Irina I. Shelyapina (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2020)
The article is devoted to the description of the lexical-textual simulator «word-concept-image» as a methodological tool that allows to identify adequately the axiological potential of the text and provide a deep understanding of publicistic works. The logic of textual activity with the use of a simulator focused on understanding publicism is described. The algorithm of textual activity is illustrated on a specific example: the analysis of the essay.